The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/aln.0b013e31821810c7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Study Using Pooled DNA to Identify Candidate Markers Mediating Susceptibility to Postoperative Nausea and Vomiting

Abstract: Background: A family history has been established as a risk factor for postoperative nausea and vomiting (PONV), but the identities of susceptibility genes remain unknown. The goal of this study was to identify the genetic loci that may contribute to PONV susceptibility in an adult population. Methods:The authors performed a genome-wide association study involving pooling of DNA obtained from 122 patients with severe PONV and 129 matched controls. Each pool was hybridized to a single nucleotide polymorphism (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
2
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 37 publications
3
68
2
5
Order By: Relevance
“…In this study, the researchers found that intractable PONV ran in families. 21 In addition, this study confirmed an association between a single nucleotide polymorphism and PONV susceptibility.…”
Section: Patient-specific Risk Factorssupporting
confidence: 69%
See 1 more Smart Citation
“…In this study, the researchers found that intractable PONV ran in families. 21 In addition, this study confirmed an association between a single nucleotide polymorphism and PONV susceptibility.…”
Section: Patient-specific Risk Factorssupporting
confidence: 69%
“…21 As receptor sites are important in drug metabolism, and these sites are genetically determined, several studies have been conducted during the last decade. This author identified genetic studies that have been undertaken by seven additional researchers specific to a particular medication's effect and the genetic variations of a receptor.…”
Section: Geneticsmentioning
confidence: 99%
“…Individual differences in the sensitivity to, and metabolism of, antiemetic drugs were reported previously [23]. Recent reports have shown that genetic polymorphisms of several known genes, in several metabolic pathways, were associated with CINV [2,24].…”
mentioning
confidence: 92%
“…Studies have demonstrated associations between PONV and specific genetic polymorphisms, such as specific single nucleotide traits of acetylcholine M3 subtype receptors (linked to motion sickness) as well cytochrome P450 genotypes 5 responsible for rapid metabolism of many drugs and toxins. 6 These could act as valuable targets in the future for patient specific pharmacogenetic targets.…”
Section: Patient Factorsmentioning
confidence: 99%